Atharva Business College Students' Choice Regarding Bank Selection - Magar, Kabita Thapa; Adhikari, Subash; Chaudhary, Rajeshwer Prasad; Niraula, Arjun (International Journal of Atharva, 2023)
Commercial banks need to understand the things that influence prospective of customers' bank choice decisions in order to develop an effective marketing plan for gaining new clients. The purpose of this research was to examine the aspects that influence Atharva Business College students' choice of bank. In order to accomplish the stated objective, this study employed a quantitative research approach by administering questionnaires to a sample of 40 students. Descriptive statistics was used to examine the data. The study identifies six key factors that significantly influence students' choice of a bank in college. Factors include convenience in terms of location, the friendliness of staff, low service charges, the rate of interest on loans and savings, the availability of ATM services, and mobile banking options. Researchers advise banks to regularly monitor and assess customer preferences, behaviors, and expectations.